2010
DOI: 10.1590/s1983-14472010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Cotidianos de famílias de crianças convivendo com doenças crônicas: microssistemas em intersecção com vulnerabilidades individuais

Abstract: Situations of vulnerability of the environment in which a child and their family are inserted may be translated into life and development conditions. The objective of this study is to know how families perceive the situations of vulnerability and their components, related to the ecological environment, experienced by children who face chronic diseases and are hospitalized in a School Hospital in Porto Alegre, Rio Grande do Sul, Brazil. This is a quantitative research from the perspective of a descriptive explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
2
0
6
Order By: Relevance
“…A família compõe um microssistema central na vida das crianças e representa uma das mais importantes influências sobre o desenvolvimento humano nesta fase da vida (Pedroso & Motta, 2010). A partir dessa premissa, fundamentada pela abordagem bioecológica de Bronfenbrenner (1979Bronfenbrenner ( /1996, pesquisadores visam compreender fatores que afetam a qualidade das relações entre crianças e adultos, levando em conta as habilidades e necessidades dos mesmos, as quais variam ao longo do tempo e de acordo com o contexto em que a família está inserida.…”
unclassified
“…A família compõe um microssistema central na vida das crianças e representa uma das mais importantes influências sobre o desenvolvimento humano nesta fase da vida (Pedroso & Motta, 2010). A partir dessa premissa, fundamentada pela abordagem bioecológica de Bronfenbrenner (1979Bronfenbrenner ( /1996, pesquisadores visam compreender fatores que afetam a qualidade das relações entre crianças e adultos, levando em conta as habilidades e necessidades dos mesmos, as quais variam ao longo do tempo e de acordo com o contexto em que a família está inserida.…”
unclassified
“…Vulnerability is associated with the precariousness in the wide array of goods and services surrounding the disease-centered situation. The healthcare team must take into account the difficulties affecting the child and his family in order to deliver comprehensive health care based on the construction of support networks both at the hospital and home (16) .Bearing all these factors in mind, it is clearly observed that the special health care need of the CRIANES causes these children and their families to fight for their survival and also to find their place in society, which is not yet ready to properly accept them. This status causes this group to become vulnerable regarding their citizenship rights.…”
mentioning
confidence: 99%
“…Vulnerability is associated with the precariousness in the wide array of goods and services surrounding the disease-centered situation. The healthcare team must take into account the difficulties affecting the child and his family in order to deliver comprehensive health care based on the construction of support networks both at the hospital and home (16) .…”
mentioning
confidence: 99%
“…26 As frequentes hospitalizações da criança podem também originar a perda do emprego dos pais, embora haja pais que renunciem a seus empregos para poderem se dedicar exclusivamente ao cuidado e tratamento do filho. 27,28 Por incrível que pareça falar a situação hoje, a nossa situação financeira não é ruim, que eu ganhava o triplo do que eu pego hoje da pensão do Lucas, meu marido ganhava o dobro, mas a gente hoje ganha 40% do que a gente ganhava e a gente vive bem com esse dinheiro, as nossas despesas são cobertas pelo governo (Marisa).…”
Section: é Porque é Difícil Uma Mãe Ver Um Filho Desse Jeito (Selma)unclassified